2023
DOI: 10.3390/v15020339
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Fungal Virus Representing a Novel Genus in the Family Alphaflexiviridae

Abstract: Sclerotinia sclerotiorum is an ascomycetous fungus and hosts various mycoviruses. In this study, a novel fungal alphaflexivirus with a special genomic structure, named Sclerotinia sclerotiorum alphaflexivirus 1 (SsAFV1), was cloned from a hypovirulent strain, AHS31. Strain AHS31 was also co-infected with two botourmiaviruses and two mitoviruses. The complete genome of SsAFV1 comprised 6939 bases with four open reading frames (ORFs), a conserved 5′-untranslated region (UTR), and a poly(A) tail in the 3′ termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…For example, the growth rate of the S. sclerotiorum SZ-150 strain coinfected with Sclerotinia sclerotiorum hypovirus 1 and its related satellite RNA slowed, and the colony edge was abnormal [ 38 ]. The growth rate of the S. sclerotiorum AHS31 strain was reduced after being coinfected with botourmiaviruses and mitoviruses, and its pathogenicity decreased significantly [ 39 ]. Fungal infection with PlHV results in various phenotypes, ranging from a normal phenotype to stunted colonies with irregular colony edges [ 40 ], which is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the growth rate of the S. sclerotiorum SZ-150 strain coinfected with Sclerotinia sclerotiorum hypovirus 1 and its related satellite RNA slowed, and the colony edge was abnormal [ 38 ]. The growth rate of the S. sclerotiorum AHS31 strain was reduced after being coinfected with botourmiaviruses and mitoviruses, and its pathogenicity decreased significantly [ 39 ]. Fungal infection with PlHV results in various phenotypes, ranging from a normal phenotype to stunted colonies with irregular colony edges [ 40 ], which is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In all plant-infecting members of the family, except for members of the genus Platypuvirus , ORF 2–4 encode the ‘triple gene block’ proteins involved in the cell-to-cell movement ( Verchot-Lubicz et al., 2010 ), and ORF5 encodes the viral capsid protein. So far, only four alphaflexiviruses that infect three plant pathogenic fungi, including Botrytis cinerea (Botrytis virus X, BVX), Botryosphaeria dothidea (Botryosphaeria dothidea botrexvirus 1, BdBV1), and Sclerotinia sclerotiorum (Sclerotinia sclerotiorum alphaflexivirus 1, SsAFV1; Sclerotinia sclerotiorum debilitation-associated RNA virus, SsDRV), have been discovered and characterized ( Howitt et al., 2006 ; Xie et al., 2006 ; Yang et al., 2021 ; Ye et al., 2023 ).…”
mentioning
confidence: 99%
“…Recently, many novel mycoviruses have been characterized and identified in S. sclerotiorum ( Jia et al., 2021 ; Mu et al., 2018 ; Zhang et al., 2019 b). Eight reported mycoviruses in S. sclerotiorum belong to the order Tymovirales , three (Sclerotinia sclerotiorum deltaflexivirus 1, SsDFV1, SsDFV2, and SsDFV3) of which are positioned in the genus Deltaflexivirus within the family Deltaflexiviridea ( Hamid et al., 2018 ; Li et al., 2016 ; Mu et al., 2021 ), two (Sclerotinia sclerotiorum debilitation-associated RNA virus; SsDRV and SsDRV2) are assigned to genus Sclerodarnavirus within family Alphaflexiviridae ( Hu et al., 2014 ; Xie et al., 2006 ), two (Sclerotinia sclerotiorum mycotymovirus 1, and Sclerotinia sclerotiorum tymo-like RNA virus 4) are assigned to family Tymoviridae , and our group recently reported that SsAFV1 belongs to genus Botrexvirus within family Alphaflexiviridae ( Ye et al., 2023 ). Here, we report the characterization of a second botrexvirus, Sclerotinia sclerotiorum alphaflexivirus 2 (SsAFV2), in the hypovirulent strain 32–9 of S. sclerotiorum .…”
mentioning
confidence: 99%
See 1 more Smart Citation